S138 Treating idiopathic pulmonary fibrosis with the addition of co-trimoxazole. (2nd December 2011) - Shulgina, L; Cahn, A; Chilvers, E; Parfrey, H; Clark, A; Wilson, E; Twentyman, O; Davison, T; Curtin, J; Wilson, A
Abstract : Background: Idiopathic pulmonary fibrosis is a fatal condition with limited treatment options; however in a previous small study co-trimoxazole has been shown to be beneficial. Methods: In a double-blind, multi-centre study, 181 patients with usual interstitial pneumonia (n=166) or fibrotic non-specific interstitial pneumonia (n=15) were randomised to receive co-trimoxazole 960 mg twice daily or placebo for 12 months in addition to their usual care. Measurements were made of forced vital capacity (FVC), total lung capacity, total lung diffusing capacity of carbon monoxide, Medical Research Council dyspnoea score, St George's Respiratory Questionnaire and quality adjusted life years (QALYs). All cause mortality, costs and adverse events were recorded. Results: Co-trimoxazole had no effect on FVC or other measures of lung function. However in the per-protocol analysis, co-trimoxazole resulted in a significant reduction in mortality (HR of 0.2 (0.06, 0.78)), significant improvements in the symptom domain of St George's Respiratory Questionnaire (mean difference −5.30 (−11.99, 1.40) units) and QALYs gained (mean difference 0.12 (0.01, 0.22) QALYs), and a reduction in the percentage of patients requiring an increase in oxygen therapy (OR 0.05 (0.00, 0.61)) compared to placebo. Furthermore, the use of co-trimoxazole reduced respiratory tract infections. The incremental cost per QALY gained was £21 391 (52.74% probability of being below £30 000; intention to treat analysis, UK societal perspective). Conclusion: The addition of co-trimoxazole therapy to standard treatment for Idiopathic pulmonary fibrosis had no effect on lung function or disease progression but resulted in a fivefold reduction in mortality and was cost-effective at UK thresholds.